Culture jamming e seu potencial criativo no ciberespaço - Diniz, Juana Ribeiro (2010)
This work has as its study object the culture jamming, a form of contemporary activism which, through practices that blend various art techniques and a boyish trick spirit, subverts advertising messages and leads to situations that criticize media culture and the branding process that this culture helps to produce. The question more frequently discussed about jammer performances regards its revolutionary efficacy. Thus, this research intends to make an analysis of the possibilities that the cyberspace opens, as a new format, to the jammer creation. It begins delineating a panorama of jammer performance, using as major references the analyses of the following authors: Kalle Lasn, Mark Dery and Naomi Klein. The next chapter contextualizes the culture jamming in the cyberspace, using André Lemos', Lúcia Santaella's and Pierre Lévy's theories on such matter. Supported by studies about the aesthetics of technology, it was possible to draw a profile of the jammer aesthetic in the cyberspace and, in this way, to analyze some examples in order to compare their approach in the real space and the virtual one. For this topic, Derrick Kerckhove's, Lúcia Santaella's and Pierre Lévy's theories were used. The examples were chosen regarding the necessity to analyze both their diversity as their repercussion. So, the comparative analyses lead us to remark that the jammer creation in the cyberspace is still coy and not completely aware of the full possibilities offered by it. And because of the complex and dynamic aspects of the web environment, it is difficult to foresee or indicate the entire range of possibilities that the cyberspace has to offer to jammer creation. However, this research leads to believe that the better source to increase and explore the creativity inside the cyberspace is in the paths that have been opened by the cyberart. It is a longtime bet, but everything indicates that the more familiar the jammers get with the virtual space, more capable they will become to explore all the creative aspects granted by the cyberspace